SANITATION AND ENVIRONMENTAL PROBLEMS IN HASSIMESSAOUD CITY (LOWER SAHARA - ALGERIA) - Belkacem Bitat; Lamia Bouldjemar; Amina Benelmadjat (International Journal of Innovative Technologies in Social Science, 2024)
The dysfunction of the liquid waste sanitation systems is noticeable in the city of Hassi-Messaoud: wastewater stagnates in empty spaces (sludge). The consequences of this dysfunction on the living environment and the natural ecosystem are becoming more and more serious and call for appropriate decisions from all the actors involved. In addition, the development of oil activities will lead to significant changes in the environment, particularly in water resources. Industrial pollution has very negative effects on the quality of water resources. It has to be treated at the plant level, especially to remove toxic elements. This situation suggests that if nothing is done to correct the situation, pollution could become a serious cause of water shortages in the future.